IPTEKS BAGI MASYARAKAT MANAJEMEN DESA WISATA KALIBUNTUNG - Ratnaningtyas, Yohana Ari (Universitas Esa Unggul, 2018)
AbstractAdministrators at Kalibuntung Touristy Village feel that their ability and knowledge in management and tourism are very limited, therefore, it is necessary to conduct a workshop to enhance the quality of the administratos. After the participant obtained the material from the workshop, it is hoped that their skill and knowledge about management and marketing are improved. The method employed was initiated by a program socialization to create a communication as well as to help enhance the participantsÃ¢â‚¬â„¢ skill about the importance of the management system in developing touristy village. Administrators along with team identify and study the problems, the potencies and chances which then arranged in a plan and implemented as workshops aiming to improve the ability of the participants in comprehending the issues of management and tourism in enhancing the touristy village and to give practical experience in accordance with the latest development. Workshops materialsÃ¢â‚¬â„¢ are namely Management Workshop, Tourism Marketing Workshop, and Blog Management Workshop. Monitoring and evaluation are conducted to monitor all workshops, both the process of implementation and the expected results so they could be well elaborated as stated in the initial objective. The result showed that there is an improvement in the quality of the administrators in management and tourism as well as there is a blog or Facebook of the touristy village to open the market of the touristy village much better. Workshops are finalized by handing over some donations such as brochures, costumes for gamelan players (pengrawit) and sound system, witnessed by administrators of the touristy village, coordinator of gamelan players and a representative from Tourism Office Bantul. Ã‚Â Keywords: improvement of ability, management, touristy villageÃ‚Â AbstrakPengurus di Desa Wisata Kalibuntung merasa kemampuan dan pengetahuan di bidang manajemen dan pariwisata masih sangat terbatas, oleh karena itu dipandang perlu untuk melakukan pelatihan guna peningkatan kualitas pengurus. Setelah peserta mendapatkan materi pelatihan, diharapkan terjadi peningkatan kemampuan dan pengetahuan pengurus desa wisata dalam hal manajemen dan pemasaran. Metode yang dipakai didahului dengan sosialisasi program untuk menciptakan komunikasi serta membantu meningkatkan pemahaman pengurus tentang pentingnya manajemen dalam pengembangan desa wisata. Pengurus desa wisata bersama dengan tim mengidentifikasi dan mengkaji masalah, potensi serta peluang kemudian disusun rencana kegiatan berupa program pelatihan yang bertujuan untuk meningkatkan kemampuan peserta dalam memahami masalah manajemen dan pariwisata bagi pengembangan desa wisata dan memberikan pengalaman praktis sesuai dengan perkembangan terkini. Materi yang diberikan adalah Pelatihan Manajemen, Pelatihan Pemasaran Pariwisata dan Pelatihan Pengelolaan Blog. Monitoring dan evaluasi diadakan untuk memantau kegiatan ini, baik proses pelaksanaan maupun hasil yang dicapai agar sesuai dengan tujuan semula. Hasil yang diperoleh terjadi peningkatan kualitas pengurus dibidang manajemen dan pariwisata serta tersedianya blog/facebook desa wisata sehingga diharapkan dapat mengelola dan memasarkan desa wisata dengan lebih baik. Pelatihan diakhiri dengan penyerahan bantuan berupa brosur, kostum seragam pengrawit dan sound system disaksikan pengurus desa wisata, ketua kelompok pengrawit dan perwakilan dari Dinas Pariwisata Bantul.Ã‚Â Kata kunci : peningkatan kemampuan, manajemen, desa wisata